2012
DOI: 10.1158/0008-5472.can-12-0299
|View full text |Cite
|
Sign up to set email alerts
|

CD44s Regulates the TGF-β–Mediated Mesenchymal Phenotype and Is Associated with Poor Prognosis in Patients with Hepatocellular Carcinoma

Abstract: The prognosis for individuals diagnosed with hepatocellular carcinoma (HCC) remains poor because of the high frequency of invasive tumor growth, intrahepatic spread, and extrahepatic metastasis. Here, we investigated the role of the standard isoform of CD44 (CD44s), a major adhesion molecule of the extracellular matrix and a cancer stem cell marker, in the TGF-b-mediated mesenchymal phenotype of HCC. We found that CD44s was the dominant form of CD44 mRNA expressed in HCC cells. Overexpression of CD44s promoted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
188
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(194 citation statements)
references
References 50 publications
5
188
1
Order By: Relevance
“…Ju et al (42) also revealed that CD44 is required to maintain human colon cancer stemness; knockdown of CD44 expression reduced the colony forming ability and decreased the expression of Snail and Twist. Mima et al (43) demonstrated that CD44s regulate TGF-␤-mediated mesenchymal phenotype in hepatocellular carcinoma cells. Furthermore, the loss of CD44 expression abrogated TGF-␤-induced vimentin expression and mesenchymal spindle-like morphology (43).…”
Section: Coordinated Roles Of Snail and Twist In Has2-induced Csc Expmentioning
confidence: 99%
See 1 more Smart Citation
“…Ju et al (42) also revealed that CD44 is required to maintain human colon cancer stemness; knockdown of CD44 expression reduced the colony forming ability and decreased the expression of Snail and Twist. Mima et al (43) demonstrated that CD44s regulate TGF-␤-mediated mesenchymal phenotype in hepatocellular carcinoma cells. Furthermore, the loss of CD44 expression abrogated TGF-␤-induced vimentin expression and mesenchymal spindle-like morphology (43).…”
Section: Coordinated Roles Of Snail and Twist In Has2-induced Csc Expmentioning
confidence: 99%
“…Mima et al (43) demonstrated that CD44s regulate TGF-␤-mediated mesenchymal phenotype in hepatocellular carcinoma cells. Furthermore, the loss of CD44 expression abrogated TGF-␤-induced vimentin expression and mesenchymal spindle-like morphology (43). In this study, however, the treatment of HAoverproducing Has2 ⌬Neo cells with neutralizing CD44 antibody did not abrogate EMT or CSC conversion (data not shown), suggesting the involvement of a CD44-independent pathway in the control of HA-induced EMT and CSC conversion.…”
Section: Coordinated Roles Of Snail and Twist In Has2-induced Csc Expmentioning
confidence: 99%
“…Of the 150 HCC patients, 55 (36.7%) were revealed to have an E-cadherin high /vimentin low expression profile (low ability of EMT), whereas 21 (14.0%) were diagnosed with an E-cadherin low /vimentin high profile (high ability of EMT). TGF-β signaling plays a central role in EMT; treatment of HCC cell lines with TGF-β1 induced the E-cadherin low / vimentin high expression profile indicative of high ability of EMT (8). Therefore, we assessed the clinical relevance of TGF-β signaling in patients with HCC by IHC analysis of phospho-Smad2; 41 (27.3%) of 150 patients showed high phospho-Smad2 nuclear positivity.…”
Section: Emt Expression Profile In Hcc Patients and Its Correlationmentioning
confidence: 99%
“…TGF-β binds to type I and type II serine/threonine kinase receptors, resulting in the translocation of phosphorylated Smad proteins (phospho-Smad2 and 3) into the nucleus where they regulate the expression of various target genes (7). A previous study using HCC cell lines demonstrated that TGF-β signaling triggered EMT, which was characterized by E-cadherin low /vimentin high expression in vitro (8). However, the existence of a clinical association between the expression profiles of EMT markers and TGF-β signaling, and its significance in HCC patients remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the commonly-reported LCSC surface markers are EpCAM (also known as CD326), CD133, CD90 (also known as Thy-1), CD44, and CD13 (40,(46)(47)(48)(49). In addition, other surface markers have also been demonstrated to be involved, including OV6, K19, c-kit (also known as CD117), ATP binding cassette subfamily G member 2 (ABCG2), and aldehyde dehydrogenase (ALDH).…”
Section: Currently Known Lcsc Surface Markersmentioning
confidence: 99%